Perfil lipidíco, agregação plaquetária e atividade de ectoenzimas do sistema purinérgico em plaquetas de pacientes HIV positivos sob terapia antirretroviral - Rezer, João Felipe Peres (2013)
HIV infection is characterized by continuous viral replication and depletion of CD4 + T lymphocytes, leading to immunological changes and opportunistic infections by pathogens. The use of antiretroviral therapy (ART) became apparent regression of clinical manifestations, accompanied by improvement in the patient's clinical condition. Fact which indicates an increase in life expectancy. However, with the benefits of medication complications arise also related to the toxicity of these drugs. HIV infection and HAART has been strongly associated with the risk of cardiovascular disease and possible prothrombotic events. Knowing the participation of platelets as effector cells in the immune response, inflammatory and clotting and that the purinergic system comprising ectoenzymes as E-NTPDase, and 5'-nucleotidase and E-ADA besides their role in regulating levels of adenine nucleotides and nucleoside have important actions in tromboregulation hemostasis and the aim of this study was to determine the profile of platelet aggregation activity ectoenzymes in platelets and metabolic changes in HIV-infected individuals. The study included 20 control subjects (tested negative for HIV), 10 HIV individuals (seropositive for HIV without antiretroviral treatment) and 50 HIV-HAART (seropositive for HIV and treated with HAART). The results show that there was no change in the activity of the E-NTPDase for ATP hydrolysis, but there was a decrease in the hydrolysis of ADP in HIV HAART group. The activity of E-5'-nucleotidase is not changed to AMP hydrolysis in HIV HAART. However, the activity of E-ADA groups is decreased in HIV and HIV HAART, which may promote an increase in extracellular levels of adenosine. Also found increased platelet aggregation and increased LDL cholesterol and triglyceride levels in HIV HAART group, these data suggest increased risk of cardiovascular disease. Thus, the results reported here suggest that antiretroviral treatment has a significant change, both in the activity of the purinergic system ectoenzymes involved in thromboregulation, as the profile of platelet aggregation in these patients and metabolic parameters, data that can support risk hypotheses cardiovascular this group of patients and a possible cardioprotective effect of extracellular adenosine during antiretroviral treatment.